One health approach in Nepal: review of policy perspectives - Paudel, Sudarshan; Paudel, Deepak; Devkota, Anu; Jaishi, Dipendra; Dhakal, Laxman; Kandel, Jitendra; Fröeschl, Günter (Journal of Patan Academy of Health Sciences, 2025)
The One Health (OH) approach integrates human, animal, and environmental health to address complex public health risks. In Nepal, its importance is growing due to an increasing incidence of zoonotic diseases, antimicrobial resistance, rapid urbanization, and climate change. The National Health Policy 2019, One Health Strategy 2019, and Public Health Service Act 2018 provide a foundation for enhanced coordination, surveillance, and inter-sectoral collaboration. However, fragmented governance, resource constraints, poor data integration, and limited local capacity hinder desired progress. Furthermore, low public awareness and weak interdisciplinary policymaking pose additional challenges. Strengthening Nepal’s OH framework requires interdisciplinary commitments, stronger institutional linkages, robust surveillance, responsive health teams, and active community networks. Policy coherence, capacity-building, and inclusive engagement are essential for operationalizing OH and ensuring national and global health security. By aligning efforts across sectors, Nepal can harness OH’s potential to safeguard public health and build resilient systems against emerging health threats.